Creative Work ‘The story of the Markham car collection’. Exegesis: Designing a storyteller panorama tour and the user experience - Dawson, Beata (Curtin University, 2019)
This research focuses on the design and creation of a storyteller panorama tour. It showcases large physical museum objects and demonstrates how to combine digital technologies in a museum environment to engage visitors. It tells the story of the Markham car collection using panorama technologies, including interactive digital rich multimedia resources. The research also provides a methodological reference on how to evaluate the user experience of museum-related digital productions or projects.